2020
DOI: 10.1155/2020/6352315
|View full text |Cite
|
Sign up to set email alerts
|

Negative Predictive Value of Human Papillomavirus Testing: Implications for Anal Cancer Screening in People Living with HIV/AIDS

Abstract: Objectives. People living with HIV/AIDS (PLWHA) have an increased incidence of anal squamous cell carcinoma. Since high-risk human papillomavirus (hrHPV) is the primary cause, hrHPV DNA testing may play an important role in anal cancer screening. This study aims to determine the negative predictive value (NPV) of hrHPV testing in PLWHA as well as factors that may lead to false-negative results. Methods. Anal swabs were collected for cytology and Cobas® 4800 HPV test for 14 hrHPV types. Patients underwent conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This was unexpected given high hrHPV prevalence among MSM LWH inferring excellent positive predictive value of true hrHPV infection, but correspondingly poor specificity [ 25 ]. Nonetheless, Wang et al reported a 92% negative predictive value of hrHPV positivity for anal HSIL among 156 PLWH, with no anal cancers detected [ 26 ]. In a separate prospective study, when incorporated into anal cancer screening algorithms for high risk groups, hrHPV testing increased sensitivity for histologic HSIL and anal cancer, though decreased specificity when compared to anal cytology alone [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was unexpected given high hrHPV prevalence among MSM LWH inferring excellent positive predictive value of true hrHPV infection, but correspondingly poor specificity [ 25 ]. Nonetheless, Wang et al reported a 92% negative predictive value of hrHPV positivity for anal HSIL among 156 PLWH, with no anal cancers detected [ 26 ]. In a separate prospective study, when incorporated into anal cancer screening algorithms for high risk groups, hrHPV testing increased sensitivity for histologic HSIL and anal cancer, though decreased specificity when compared to anal cytology alone [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study of hrHPV PCR testing in HIV‐positive MSM established a high sensitivity (98.4–100%) and low specificity (26–28.9%) in the identification of AIN2/3 74 . Another found a negative predictive value of 92% in a cohort of HIV‐positive patients 75 . This reflects the high prevalence of HPV infection in HIV‐positive MSM, which complicates the utility of HPV screening; in one meta‐analysis, prevalence of any HPV and HPV16 in HIV‐positive MSM was estimated to be 81% and 30%, respectively 76 .…”
Section: Preventionmentioning
confidence: 99%
“…74 Another found a negative predictive value of 92% in a cohort of HIV-positive patients. 75 This reflects the high prevalence of HPV infection in HIV-positive MSM, which complicates the utility of HPV screening; in one meta-analysis, prevalence of any HPV and HPV16 in HIV-positive MSM was estimated to be 81% and 30%, respectively. 76 Further investigation is warranted regarding the use of HPV screening in immunologically intact men and women, particularly in the MSM population who are also at an increased risk for anal HPV acquisition.…”
Section: Anal Cytologymentioning
confidence: 99%
“…22,23 Existing screening strategies used for cervical cancer have been studied for anal cancer, including anal cytology [aCyt] and HPV DNA from an anal swab, with some studies suggesting potential benefit 22,23 and others not. [24][25][26] The prevalence of oncHPV infection is high among MSM. 27,28 Thus, oncHPV testing alone may be highly sensitive, but has poor specificity for anal cancer screening among MSM.…”
Section: Introductionmentioning
confidence: 99%